Effect of oxalic acid on rumen function and microbiota in sheep fed a low quality diet - Benbati M.; Belenguer A.; Hervás G.; Toral P.G.; Frutos P. (Feeding and management strategies to improve livestock productivity, welfare and product quality under climate change, 2013)
Oxalic acid is a potentially toxic compound present in many plants that can be consumed by ruminants in some less-favoured areas. However, consequences of its consumption on the rumen function and microbiota remain unclear. Five ewes receiving low quality grass hay were daily dosed 0.6 mmol of oxalic acid/kg body weight through a rumen cannula for 14 days. On days 0 (before starting the dosing), 4, 7 and 14 of administration, alfalfa hay and barley straw were in situ incubated, and samples of rumen digesta were collected throughout the day (0, 3, 6 and 9 h after morning meal). The rumen bacterial community was studied using the terminal restriction fragment length polymorphism (T-RFLP) technique. Oxalic acid administration reduced the dry matter disappearance of alfalfa hay on days 7 and 14 and of barley straw on day 7. Neither pH values nor total volatile fatty acid concentrations were affected. Nevertheless, ammonia and butyrate concentrations were reduced and molar proportions of acetic and propionic acids were increased. Although oxalic acid did not modify rumen bacterial diversity, it altered the structure of the community and the relative frequencies of a number of TR-fragments over the total peak area. Most of these changes were reversed at the end of the experiment (on day 14). Therefore, despite the slight negative effect on ruminal degradation, the lack of a clear detrimental effect on rumen fermentation and the recovery of the initial values in some parameters suggest an adaptation of the ruminal microbiota within 2 weeks.
14. International Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2012/06/15-17, Hammamet (Tunisia)